Integrative Mathematical Frameworks for Biological Systems: Applications of Queueing Theory and Fractal Geometry in Pathology and Genomic Analysis - A Mageed, Ismail (Biocompounds, 2025)
Together, fractal geometry, information theory (especially queueing theory), and educatory mathematics provide a potent multidisciplinary approach to examine complicated biological systems, especially in pathology and genetic data. This study looks at how these different but related disciplines can help us better grasp how diseases progress, genetic mutations, and the natural complexity of biological structures work. Educatory mathematics gives the basic quantitative tools, information queueing theory helps understand how biological signals and resources are processed and flow, and fractal geometry clarifies the complex and self-similar patterns typical of biological systems. We will go over how this synergistic method helps make new diagnostic tools, predict disease outcomes, and move personalized medicine forward. We'll also talk about its theoretical basis and how it can be used in real life.